Did India's ecological fiscal transfers incentivize state governments to increase their forestry budgets?. (31st March 2020) - Busch, Jonah; Kapur, Avani; Mukherjee, Anit
Abstract: Ecological fiscal transfers (EFTs) involve higher levels of government distributing funds to lower levels of government based on ecological indicators. In 2015 India established the world's largest system of EFTs when its 14th Finance Commission added forest cover to the formula that determines the amount of tax revenue the Union government distributes annually to each state. Here we gather state-by-state data on forestry budgets to assess whether India's EFTs incentivized states to protect and restore forests as evidenced by increases to their forestry budgets. We find that states increased their forestry budgets by 19% in absolute terms in the three years after the introduction of EFTs relative to the three years prior. However, forestry budgets as a share of overall state budgets shrank by 16% after the introduction of EFTs, from 0.99% to 0.83%. Furthermore, states that obtained a larger share of their budget from EFTs did not disproportionately increase their forestry budget. Taken together, this suggests the introduction of EFTs has not yet led states to increase their forestry budgets. We develop a causal chain that suggests two reasons this could be: (1) low expectations on the part of state government officials that EFTs would continue in such a way that increases in forest cover would be rewarded with increases in revenue; and/or (2) insufficient motivation to increase forestry budgets as an investment in future revenue from EFTs. The 15th Finance Commission has plausibly addressed low expectations by keeping forests in the tax revenue distribution formula for another period and updating the year for which forest cover is measured from 2013 to 2017. It has plausibly addressed insufficient motivation by increasing the weight on forests in the formula from 7.5% to 10%. Future research can show whether these modified EFTs incentivize states to increase forest protection and restoration.